IMPROVING THE WAYS OF ISLAMIC CREDITS AND THEIR APPLICATION TO UZBEKISTAN - Urinov Feruz Sadriddin Ugli (Scholar Express Journals, 2023)
This article describes Uzbekistan integration into the global financial services industry in the development of the digital economy context: the legal framework for the activities of takaful companies, current issues in the implementation of these services in our country, and their solutions. Also, analyzing the relevant literature analyzes the scientific works of many foreign economists on forming integrated corporate structures by ensuring integrating the banking and financial system and industries.In addition, Islamic credits and their application to Uzbekistan, many proposals and recommendations have been developed
Keywords: Islamic banking; digital economy; global financial services